The impact of theory of mind barriers in interpreting illustrations used in primary school early readers: four brief case studies of false-belief scenarios. Issue 2 (3rd April 2021) - Donner, Kelley
Abstract: Theory of mind skills are critical to understanding and interpreting many illustrations in primary school literature especially those which are used in material for the purpose of learning to read. Unfortunately, children who learn to read at an early age as well as mainstreamed children, such as those with autism, often have grave deficiencies in theory of mind skills which is necessary in order to understand first- and second-order perspective narratives. Thirty-one early readers were analysed for first- and second-order perspectives as well as for the possibility of first- and second-order false-belief scenarios. Results showed that there is a high probability that children will be confronted with early readers that require complex theory of mind skills for comprehension. In addition, four early readers were examined in more detail in case studies to see how the relationship of text to illustrations as well as the composition of the illustrations themselves either aided comprehension or increased the possibility of false belief scenarios. Finally, various tools for increasing visual literacy in regards to illustrations were discussed, such as the use of prolongation, speech bubbles, close-ups and text enhancement.